Early Mortality Predictors in İnfective Endocarditis Patients: A Single-Center Surgical Experience - Üstünışık,Çiğdem Tel (2022)
ABSTRACT Introduction: Infective endocarditis is a disease that progresses with morbidity and mortality, afecting 3-10 out of 100,000 people per year. We conducted this study to review the early outcomes of surgical treatment of infective endocarditis. Methods: In this retrospective study, 122 patients who underwent cardiac surgery for infective endocarditis in our clinic between November 2009 and December 2020 were evaluated. Patients were divided into two groups according to in-hospital mortality. Demographic, echocardiographic, laboratory, operative, and postoperative data of the groups were compared. Results: Between November 3, 2009, and December 7, 2020, 122 patients were operated for infective endocarditis in our hospital. Emergency surgery was performed in nine (7.3%) patients. In-hospital mortality occurred in 23 (18.9%) patients, and 99 (81.1%) patients were discharged. In-hospital mortality was related with older age, presence of periannular abscess, New York Heart Association class 3 or 4 symptoms, low albumin level, high alanine aminotransferase level, and longer cross-clamping time (P<0.05 for all). Conclusion: The presence of paravalvular abscess was the most important prognostic factor in patients operated for infective endocarditis.